2020
DOI: 10.1038/s41589-020-0646-2
|View full text |Cite
|
Sign up to set email alerts
|

Sterols in an intramolecular channel of Smoothened mediate Hedgehog signaling

Abstract: Smoothened (SMO), a class-Frizzled G protein-coupled receptor (class-F GPCR), transduces the Hedgehog signal across cell membrane. Sterols can bind to its extracellular cysteine rich domain (CRD) and to several sites in the 7 transmembrane helices (7-TMs) of SMO. However, the mechanism how sterols regulate SMO via multiple sites is unknown. Here we determined structures of SMO–G i complexes bound to the synthetic SMO agonist (SAG) and to 24( S ),25-epoxycholesterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 54 publications
4
70
2
Order By: Relevance
“…A year later, Qi et al [135] solved more structures of WT and SMO-Gi complexes with several oxysterols and an agonist, SAG, bound (PDB:6XBM). In this way they discovered more, interconnected binding sites, which seem to allow for transfer through the receptor, from the deep 7TM pocket outwards to the CRD.…”
Section: Smo Receptor Structurementioning
confidence: 99%
“…A year later, Qi et al [135] solved more structures of WT and SMO-Gi complexes with several oxysterols and an agonist, SAG, bound (PDB:6XBM). In this way they discovered more, interconnected binding sites, which seem to allow for transfer through the receptor, from the deep 7TM pocket outwards to the CRD.…”
Section: Smo Receptor Structurementioning
confidence: 99%
“…Cholesterol Activity regulation [8,9] Activity and changes in conformation [10], Modulation of substrate binding affinity [11] Channel inhibition [12] Activation [13], Signalling [14,15], Stability [16,17], Allosteric regulation [18], Lower affinity ligand binding [17], Oligomerisation [19][20][21][22][23] PA Activity [24] Stabilisation [25] PE Dimer formation and function [26], Dimer formation [27], conformer stability [28] Conformer stabilisation and channel desensitisation [29] Agonist and antagonist binding affinities [30], Increase G protein coupling [31,32] Protein assembly [33] PC Dimerisation [34], β-arrestin interaction and function [35], Increase G protein coupling [31] PG Oligomerisation and function [36] Conformer stabilisation and channel desensitisation [37] Increase G protein coupling [30,38], Active conformer stability [39], β-arrestin interaction and function [35], Decrease G protein coupling [31] PS Dimer formation [27], Stabilisation [25], Dimerisation [34], Decrease G protein coupling [31] PI Dimer formation and function…”
Section: Lipid Entitymentioning
confidence: 99%
“…Cholesterol directly affects the ligand-binding ability of several GPCRs, including the subtype 2 galanin receptor and the serotonin 1A receptor [95], and there is evidence that cholesterol also plays a role in GPCR signalling, for example, increasing basal activity of the cannabinoid 2 receptor [14]. In the recent study of the class F GPCR, Smoothened, cholesterol is revealed to traffic through a channel in the receptor and play a fundamental role in receptor activation [13].…”
Section: Gpcrs and Cholesterolmentioning
confidence: 99%
“…In the pathway "on" state, Hh ligands bind to and inactivate the 12-transmembrane sterol transporter PATCHED1 (PTCH1), which releases SMO from PTCH1-mediated inhibition 4 . This process allows SMO to access its endogenous sterol ligands and undergo an activating conformational change [11][12][13][14] . Once activated, SMO blocks PKA-C-mediated phosphorylation of GLI [15][16][17][18] , a key step that likely occurs within the tiny cell-surface compartment formed by the primary cilium [19][20][21] .…”
Section: Introductionmentioning
confidence: 99%